(untitled) (UTM Press - Edited Book, 2025)
This book provides a comprehensive exploration of optimization techniques in electric power distribution systems, addressing the growing complexity, evolving energy demands, and integration of emerging technologies in modern grids. Beginning with a clear overview of operational challenges such as power quality disturbances, environmental vulnerabilities, insulation degradation, grounding integrity, and the impact of distributed energy resources, it establishes a strong contextual foundation for readers. The subsequent chapters progress through a structured sequence of solutions, including fault classification using signal processing, lightning protection design, advanced insulation materials, power quality monitoring, economic dispatch optimization, harmonic mitigation, network reconfiguration, voltage stability improvement, and hybrid microgrid optimization. By combining theoretical principles with practical applications, simulation tools, and laboratory-based insights, the book bridges the gap between academic knowledge and engineering practice. It offers a multidisciplinary approach that spans power engineering, materials science, computational intelligence, and smart grid technologies. Designed for students, engineers, and researchers, it not only equips readers with current methods but also highlights future directions in AI-driven fault detection, adaptive protection, advanced insulation development, and real-time grounding optimization, positioning it as both a reference for today’s challenges and a guide for next-generation power distribution solutions.